2022
DOI: 10.6004/jnccn.2022.0002
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines® Insights: Multiple Myeloma, Version 3.2022

Abstract: The NCCN Guidelines for Multiple Myeloma provide recommendations for diagnosis, initial workup, treatment, follow-up, and supportive care for patients with various plasma cell neoplasms, including multiple myeloma. These NCCN Guidelines Insights highlight some of the important updates/changes specific to the treatment of patients with multiple myeloma in the 2022 version of the guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 34 publications
1
94
0
3
Order By: Relevance
“…From these findings IMPEDE score and SAVED score were recommended to be utilized as a VTE risk stratification tool. 47 Moreover, they should be employed in prospective studies looking into investigating VTE prophylaxis strategies in MM patients.…”
Section: Thrombo-hemorrhagic Risk Factors and Risk Stratificationmentioning
confidence: 99%
“…From these findings IMPEDE score and SAVED score were recommended to be utilized as a VTE risk stratification tool. 47 Moreover, they should be employed in prospective studies looking into investigating VTE prophylaxis strategies in MM patients.…”
Section: Thrombo-hemorrhagic Risk Factors and Risk Stratificationmentioning
confidence: 99%
“…The advantages of zoledronic acid (4 mg) include lower mean skeletal morbidity rate, increased median time to first SRE, and reduced risk of developing an SRE compared with pamidronate (90 mg) [ 109 ]. BPs are recommended as standard treatment of MM patients with either osteolytic bone lesions or osteopenia in many current guidelines, including those from the National Comprehensive Cancer Network (NCCN) [ 110 ], the American Society of Clinical Oncology (ASCO) [ 111 ], the Mayo Clinic [ 112 ], the European Society for Medical Oncology (ESMO) [ 113 ], and the International Myeloma Working Group (IMWG) [ 11 ]. Zoledronic acid or pamidronate once monthly, at least for the first 1 to 2 years, is recommended for almost all patients with MM who have evidence of MBD [ 11 , 111 , 112 , 113 ] ( Table 1 ).…”
Section: Current Myeloma-related Bone Disease Treatmentmentioning
confidence: 99%
“…More recently, the MAIA study including patients ineligible for auto-HSCT due to age or comorbidities showed that adding daratumumab to RD (DRD) led to a 47% and 32% reduction in the risk of progression and death, respectively, compared to RD alone [ 50 ]. Given these results, both VRD and DRD have been established as the preferred therapeutic options for patients with newly diagnosed MM who are not eligible for auto-HSCT [ 51 ].…”
Section: Immunomodulatory Drugs (Imids)mentioning
confidence: 99%